THE USE OF NUMBER HEADS TOGETHER (NHT) IN TEACHING SPEAKING FOR JUNIOR HIGH SCHOOL - Regina Rahmi; Mulyadi Syahputra (English Education Department, 2015)
This research is about the use of Number Head Together (NHT) in Teaching Speaking for Junior High School. The research problem for the study are (1) How is the use of Number Heads Together in Teaching at Junior High School, (2) What are the teacher obstacles during the use of Number Heads Together (NHT) in teaching speaking for Junior High School. The objective of the study are: (1) to figure out the use of Number Heads Together (NHT) in teaching speaking for Junior High School, (2) To find out the teacher obstacles during the use of Number Heads Together (NHT) in Teaching Speaing for Junior High School. In order to get the data, the resercher used observation sheet and Interview Guide. This research took place in SMP Muhammadiyah 1 Banda Aceh. Through the research, it was found that; (1) the use of Number Heads Together (NHT) in teaching speaking follow the steps they are, greeting, reviewing, explaining, numbering, questioning, discussing, answering. (2). There are some obstacles that the teacher faced during the use of Number Heads Together (NHT) they are: the difficulties in making the group which consist of various proficiency and the lack of students trust to the member of the groups answers.